Assessing the relationship between advertisement and consumer buying behavior : a case study of consumer of Coca-Cola in Kathmandu, Nepal - Paudel, Prabina; Ransom, Lakeesha K.; Badir, Yuosre; Tocquer, Gerard A.; King{u2019}s Scholarship (2021)
Purpose: The objective of this study is to assess the relationship between advertisement and consumer buying behavior, and to test how the Moderating variable celebrity endorsement and honest advertising influence the relation between the independent and dependent variable. Methodology: Collection of data was done through questionnaires. A total of 297 responses from the consumer of Coca-Cola in Kathmandu Nepal was used for this study. Multiple regression analysis was performed on the data. Findings: The results from the regression analysis indicate that outdoor, print, and online advertising assert a significantly positive influence on buying behavior of consumer. Further while showing the interaction between Moderating and independent variable out of 4 hypotheses developed during the research, 1 hypothesis is rejected i.e., print*celebrity endorsement. Positive relationship between celebrity endorsement on purchasing behavior of consumer was also found. Implications: This study provides a meaningful contribution to the advertising company for the Coca-Cola especially in Kathmandu, Nepal. Furthermore, Coca-Cola company, Bottlers Nepal and the advertising agency for Coca-Cola can use the findings to comprehend the relationship between the advertising media and purchasing behavior of consumer. Advertisers should choose the best media to broadcast their advertisement and to reach the target audience. Novelty: This research adds to the literature on different advertising media and on overall advertisement by examining the impact on purchasing behavior of consumer.
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2021
Keywords: Advertising -- Psychological aspects -- Case studies; Consumer behavior -- Nepal -- Kathmandu; Advertising -- Nepal -- Kathmandu